The doctor and the diva - McDonnell, Adrienne (New York : Pamela Dorman Book/Viking, 2010)
Building a successful career by helping couples to conceive, an early twentieth-century obstetrician makes a risky decision after meeting a talented opera singer whose infertility issues prompt her to leave her husband and pursue a career abroad.
Keywords: Women singers -- fiction; Opera -- Fiction; Obstetricians -- Fiction; Love stories